Makri, Despina - (:unkn) unknown (My University, 2026)
Despina Makri is currently a PhD Candidate at the Cyprus University of Technology, Department of Civil Engineering and Geomatics, focusing on seagrass habitat mapping using advanced remote sensing techniques. She holds a BSc in Marine Sciences (2016) and an MSc in Geography and Applied Geoinformatics (2018) from the University of the Aegean. Since 2015, she has participated in research projects at the University of the Aegean related to marine spatial planning and satellite-based seagrass mapping. From 2017 to 2018, she worked as a Teaching Assistant at the Computer Lab of the University of the Aegean. Between 2019 and 2021, she served as a Research Assistant at the Cyprus University of Technology under the Marie Skłodowska-Curie Actions RISE project, focusing on the processing of Sentinel-1 satellite data to develop hazard risk maps for landslides and subsidence. Since 2021, she has been employed as a Research Associate at the Cyprus University of Technology, contributing to the Framework Partnership Agreement on Copernicus User Uptake (FPCUP). Within this framework, she has organized and contributed to outreach and educational activities, workshops, and events promoting Copernicus Earth Observation services to the public, students, educators, and professionals. Since 2022, she has also been working as a Research Assistant at the ERATOSTHENES Centre of Excellence, where she contributes to projects related to marine safety and security, communication, dissemination, and demonstration activities. She is fluent in English (C1–C2) and a native speaker of Greek. Her research expertise lies in remote sensing and geoinformatics, with proficiency in tools such as Google Earth Engine, ArcGIS Pro, QGIS, ENVI, ERDAS, and SNAP, as well as experience in machine learning methods for environmental mapping. She also has significant experience in science communication, public engagement, and stakeholder collaboration.